Thin‐Film Solar Cells: Cation Substitution in Earth‐Abundant Kesterite Photovoltaic Materials (Adv. Sci. 4/2018). Issue 4 (19th April 2018) - Li, Jianjun; Wang, Dongxiao; Li, Xiuling; Zeng, Yu; Zhang, Yi
Abstract : Low‐cost and environmentally friendly kesterite structural Cu2 ZnSn(S, Se)4 (CZTSSe) thin‐film solar cells have experienced a significant increase in power conversion efficiency from about 5% to a record of 12.6%. To further improve device performance, various cation substitution technologies have been proposed to modify the electronic and optical properties of the kesterite light absorber layer. In article1700744, Yi Zhang and co‐workers review recent cutting‐edge research focusing on various cation substitution methods.